Nanosecond ligand migration and functional protein relaxation in ba3 oxidoreductase: Structures of the B0, B1 and B2 intermediate states - Nicolaides, Antonis; Soulimane, Tewfik; Varotsis, Constantinos (My University, 2016)
Nanosecond time-resolved step-scan FTIR spectroscopy (nTRS 2 -FTIR) has been applied to literally probe the active site of the carbon monoxide (CO)-bound thermophilic ba3 heme-copper oxidoreductase as it executes its function. The nTRS 2 - snapshots of the photolysed heme a3 Fe-CO/CuB species captured a "transition state" whose side chains prevent the photolysed CO to enter the docking cavity. There are three sets of ba3 photoproduct bands of docked CO with different orientation exhibiting different kinetics. The trajectories of the "docked" CO at 2122, 2129 and 2137 cm- 1 is referred to in the literature as B2, B1 and B0 intermediate states, respectively. The present data provided direct evidence for the role of water in controlling ligand orientation in an intracavity protein environment.
Keywords: Cytochrome c oxidase; Dynamics; Time-resolved step-scan FTIR